Factor analysis of Thai students’ innovator and entrepreneur competency - Chaemchoy, Sukanya (Kasetsart Journal of Social Sciences, 2023)
Student outcomes are the goal of education. In a rapidly changing world, students must equip innovator and entrepreneur competencies. This study aimed to develop and validate students’ innovator and entrepreneur competencies through exploratory (EFA) and confirmatory factor analysis (CFA). Data were gathered through a questionnaire from a sample of 2,008 students from 80 different-sized schools. Results of EFA revealed that nine factors and 49 indicators were explored, with factor loadings ranging from .504 to .985. The nine factors included: (1) questioning; (2) apophenia; (3) pursuing multiple streams; (4) observing; (5) obsessive notetaking; (6) experimenting; (7) idea networking; (8) innovative entrepreneurial leadership; and (9) social, environmental, and economic responsibility and sustainability (SEERS). CFA results showed an acceptable fit of the 9-factor model with fit indices: χ2 = 3,372.623, df = 1091, p = .000, χ2/df = 3.091, CFI = .919, TLI = .913, RMSEA = .046, and SRMR = .044. Implications and further research were discussed.